(untitled) (Bangladesh Journal of Medical Science, 2021)
Background: Cancer of the cervix is the most common cause of cancer-related deaths amongst women in India. Apart from the availability of healthcare services, awareness and attitude, the cornerstone of public health measures such as screening and vaccination are useful in the control of cervical cancer. There is a lack of studies regarding cervical cancer in the selected region. Objectives: To assess the knowledge of cervical cancer and its associated factors amongst rural women in a densely populated state of Northern India. Methodology: This cross-sectional study was undertaken for a period of one year, i.e., from April 2018 to March 2019, in five randomly selected villages of the Bakshi Ka Talab Block of District Lucknow, Uttar Pradesh. Systematic random sampling was performed to include females aged 15 years and above by a house to house survey. Trained social workers interviewed the consenting participants using a self-structured, pretested and validated questionnaire. The suitable statistical test was used to analyze the data. Results: The majority of the participants (n=300) were aged between 20- 24 years, and the mean age was 28.5 years. Sixty-four per cent of the females were married, and round 43.7% belonged to lower socioeconomic class. Nearly one third reported to have not heard of cervical cancer previously. The knowledge of the various aspects of cancer cervix varied from 3.2% to 55.3%. The most frequently recognized risk factors were early pregnancy (15.7%), giving birth to ≥ 3 children (13.2%) and early sexual initiation (11.7%). Majority of respondents (56.4 per cent) reported weakness to be the most common effect of leucorrhoea. Nearly half of females falsely perceived the actual cause of the leucorrhoea as excess heat in the body. None of the participants had either undergone screening for cervical cancer or had received HPV vaccination despite the availability of healthcare facilities within 30 kilometres. The educational and socioeconomic status were found to be significant predictors of knowledge of cervical cancer on multivariate logistic regression analysis Conclusion: A general lack of awareness has been noted regarding cervical cancer in the study population. None of the participants had undergone screening for cancer cervix or had been administered HPV vaccination, which points to a lack of healthcare utilisation. There is a need to sensitize the target population to the menace of cervical cancer and the usefulness of screening and HPV uptake. Bangladesh Journal of Medical Science Vol.20(4) 2021 p.790-795